A European Mandate for Financial Sector Supervisors in the EU. (IMF Working Papers; Working Paper ;, 2009)
The EU is deliberating the introduction of an explicit "European mandate" for financial sector supervisors to supplement national mandates. Suggestions are made on (i) the formulation of a European mandate; (ii) the policy areas to which it should apply; (iii) which institutions should be given a European mandate; (iv) the legal basis for the mandate; (v) how to implement the mandate in practice; and (vi) how to achieve accountability for fulfilling a European mandate. Decisions on these issues are needed if the introduction of a European mandate is to have a substantive positive effect.